2013
DOI: 10.1098/rspb.2013.1729
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction spontaneously highlights visual saliency map

Abstract: Attention is intrinsic to our perceptual representations of sensory inputs. Best characterized in the visual domain, it is typically depicted as a spotlight moving over a saliency map that topographically encodes strengths of visual features and feedback modulations over the visual scene. By introducing smells to two well-established attentional paradigms, the dot-probe and the visual-search paradigms, we find that a smell reflexively directs attention to the congruent visual image and facilitates visual searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…Essentially, it seems odours prime visual representations of matching objects, thus making them more salient and more difficult to mask. Previous studies have shown that olfactory-visual integration serves to enhance perception when olfactory and visual information is congruent (Chen et al, 2013;Robinson et al, 2013). The current study builds on these previous findings by showing that cross-modal associations between odours and their corresponding visual objects can enhance object identification when visual awareness is disrupted.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Essentially, it seems odours prime visual representations of matching objects, thus making them more salient and more difficult to mask. Previous studies have shown that olfactory-visual integration serves to enhance perception when olfactory and visual information is congruent (Chen et al, 2013;Robinson et al, 2013). The current study builds on these previous findings by showing that cross-modal associations between odours and their corresponding visual objects can enhance object identification when visual awareness is disrupted.…”
Section: Discussionsupporting
confidence: 60%
“…Surprisingly, there has been little focus on gender differences in multisensory integration between olfaction and other modalities, despite accumulating research on interactions between olfaction and vision. Several olfactory-visual experiments have been conducted with a majority of female participants (Chen et al, 2013;Seo, Roidl, Muller, & Negoias, 2010;Seo, Arshamian, et al, 2010;Zhou et al, 2012), so it is possible that previous results have been driven by larger multisensory effects in females than males.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be interesting to see if the newer paradigms of olfactory testing offer significant benefits. From a broader perspective, the study of olfaction sits at the intersection of many vibrant disciplines, including neuroscience, genetics, and immunology [77,78]. For the AD field, animal model studies, some employing highly innovative techniques [79], are yielding important insights; neurogenesis within the olfactory structures holds treatment potential [80]; the possibility that biopsy of olfactory mucosa might aid early diagnosis is again under discussion [2•, 34].…”
Section: Discussionmentioning
confidence: 99%